The Effect of Financing Distribution, NoSn-Performing Financing (NPF), and Financing to Deposit Ratio (FDR) on the Profitability of BTN Syariah Bank (2019–2024) (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the influence of financing distribution, Non-Performing Financing (NPF), and Financing to Deposit Ratio (FDR) on the profitability of BTN Syariah Bank during the 2019–2024 period. The study employs a quantitative research design using secondary data obtained from the bank’s annual financial statements. Profitability is measured using net profit as the dependent variable, while financing distribution, NPF, and FDR serve as independent variables. Data analysis is conducted using multiple linear regression techniques, preceded by classical assumption tests including normality, multicollinearity, heteroscedasticity, and autocorrelation tests to ensure model validity. The results indicate that financing distribution has a positive and statistically significant effect on bank profits, suggesting that effective allocation of financing contributes to higher earnings. Conversely, NPF shows a negative and significant impact on profitability, reflecting the adverse effect of financing risk on bank performance. FDR is found to have a significant effect on profitability, indicating the importance of liquidity management in optimizing profit generation. Simultaneously, financing distribution, NPF, and FDR significantly affect the profitability of BTN Syariah Bank. These findings highlight the critical role of financing management and risk control in enhancing the financial performance of Islamic banks.